Business model viability of Galileo Commercial Service - Skournetou, Danai (2013)
Currently, the business of location based service providers largely depends on the existing Global Navigation Satellite Systems (GNSSs), i.e. GPS and recently also GLONASS. Not only are these two systems operated under the discretion of the US and Russian military, respectively, but they also give only best effort guarantees on accuracy and availability. Because of this and given that LBS providers increasingly rely on positioning information, EU is preparing the launch of Europe’s own GNSS platform, Galileo, which is expected to be fully operational around 2020. Besides the free-of-charge basic service, a Commercial Service (CS) with advanced characteristics will be offered at a premium-rate to service providers. The business case behind the launch of Galileo assumed that part of the investments would be recouped by having service providers pay for the enhanced characteristics of CS, i.e. higher positioning accuracy, signal au- thentication capability and service guarantee. However, as yet, it is still highly unclear whether service providers are in fact interested to pay for accessing CS signals, especially because the access to civil satellite navigation signals has been traditionally free-of-charge. Motivated by the lack of research in this area, this thesis seeks an answer to the question “What are the factors contributing to the willingness of service providers to adopt the future Galileo Commercial Service?” To answer this, we analyzed secondary data through desk research as well as con- ducted in-depth interviews with key stakeholders. Specifically, we found that the factors contributing to the willingness of service providers to adopt CS are the key value drivers, other value determinants, demonstrated usefulness, ap- proaches alternative to Galileo CS, and reverse salients. In overall, it appears that service providers are reluctant to make any serious preparations for adopt- ing CS, as they indicate there are too many uncertainties. In order to increase the chances of adoption, we suggest clarifying the value proposition of CS as well as creating awareness of it early on and focusing attention either on getting governments on board to create trust and reputation for CS or on service pro- viders directly.